LITERATURE REVIEW: THE EFFECT OF ATRAUMATIC CARE ON ANXIETY IN CHILDREN DURING HOSPITALIZATION - Valentina Febrianti; Dwi Nurjayanti; Ucik Ernawati (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Valentina Febrianti, 2025, “literature review: The Effect of Atraumatic Care on Children's Anxiety During Hospitalization.” Advisor: Dwi Nurjayanti S.ST., M.Kes. Undergraduate Program in Nursing, Buana Husada Health Sciences College, Ponorogo.Children who undergo hospitalization often experience psychological impacts, such as anxiety, fear, sadness, and anger. Anxiety experienced by children while in the hospital can hinder the treatment process and make children uncooperative. Atraumatic care is a nursing approach that aims to minimize physical and psychological trauma in children during hospitalization. This study aims to determine the effect of atraumatic care in reducing anxiety in children who are hospitalized through a literature review study. This study uses a literature review method by analyzing 30 articles published in 2020 to 2024, both from national and international journals. The results of the study showed that the influence of atraumatic care, such as play therapy, the use of audiovisual media, parental involvement in care, and modification of the hospital environment to be child-friendly, were proven to be effective in reducing anxiety levels in children undergoing hospitalization. Most of the articles reviewed showed a significant decrease in children's anxiety levels after being given atraumatic care intervention.From the results of this literature review, it can be concluded that the influence of atraumatic care is very important and effective in helping to reduce anxiety in children during hospitalization. Therefore, the implementation of atraumatic care is expected to be part of the standard of child nursing services in hospitals in order to create a comfortable, child-friendly, and minimally traumatic environment.